2022
DOI: 10.1515/cclm-2022-1090
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of circulating tumor markers

Abstract: Tumor markers are a heterogeneous group of substances released by cancer cells into bloodstream, but also expressed by healthy tissues. Thus, very small concentrations can be present in plasma and serum from healthy subjects. Cancer patients tend to show increased levels correlating with tumor bulk, but false positive results could be present in patients with benign conditions. The correct interpretation of TM results could be challenging and many factors should be considered, from pre-analytical conditions to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…Serum biomarkers could supply a precise evaluation to diagnose and predict the various tumors for survival improvements ( 12 ). With an improvement in technology of liquid biopsy, a wide variety of public literature has confirmed that tumor-specific proteins and RNAs that are encapsulated in exosomes exhibit enormous potentially valuable and promising predicable abilities in the diagnosis and prognosis judgment of a great many diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Serum biomarkers could supply a precise evaluation to diagnose and predict the various tumors for survival improvements ( 12 ). With an improvement in technology of liquid biopsy, a wide variety of public literature has confirmed that tumor-specific proteins and RNAs that are encapsulated in exosomes exhibit enormous potentially valuable and promising predicable abilities in the diagnosis and prognosis judgment of a great many diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Literature states development/presence of tumours can be detected by (a) circulating tumour markers that are released by the tumour mass in the body fluids and stools, while (b) tumour tissue markers that are presented on the tumour cells [19–21]. The tumour cells and cellular components in peripheral blood or other body fluids such as serum, plasma, saliva, urine, tears, can be collected/sampled for the purpose of analysing tumour biology in the form of a liquid biopsy [22–24]. Currently in clinical settings, presence and levels of tumour markers in body fluids are assayed to primarily (a) detect the cancer type, (b) to assess the therapy (chemotherapy, radiotherapy and others) response and management and (c) for recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…As tumors grow, their levels increase, which are many times higher than normal human bodies. 9 The aforementioned characteristics of cancer biomarkers give them the power to indirectly reflect tumorigenesis. Moreover, cancer biomarkers often precede clinical symptoms, allowing for early tumor screening upon their detection.…”
Section: Introductionmentioning
confidence: 99%
“…They contain proteins, , cells, nucleic acids, and others, which are often found in tumor tissue, body fluids, and blood. As tumors grow, their levels increase, which are many times higher than normal human bodies . The aforementioned characteristics of cancer biomarkers give them the power to indirectly reflect tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%